Soy Isoflavones in Integrative Oncology: Increased Efficacy and Decreased Toxicity of Cancer Therapy - Sahin, Ilyas; Bilir, Birdal; Ali, Shakir; Şahin, Kazım; Küçük, Ömer (Sage Publications Inc, 2019)
Soy consumption in human diet has been linked to decreased incidence of a variety of cancers, suggesting a potential role of soy products in cancer prevention and control. Furthermore, a substantial body of evidence in the literature suggests that soy supplementation may improve the efficacy and prevent the adverse effects of cancer chemotherapy and radiation therapy. Isoflavones constitute the predominant anticancer bioactive compounds in soy. Genistein, which is the most abundant and active isoflavone in soy, has a multitude of effects on cancer cells, including inhibition of NF-kappa B activation and DNA methylation, enhancement of histone acetylation, inhibition of cell growth and metastasis, and antiangiogenic, anti-inflammatory, and anti-oxidant effects. Isoflavones are orally bioavailable, easily metabolized, and usually considered safe. In this article, we review in vitro and in vivo evidence as well as the results of clinical and epidemiological studies on the effects of soy isoflavones, with a focus on sensitization of cancer cells to chemotherapy and radiation while at the same time protecting normal cells from the harmful effects of these treatments.
Keywords: prostate cancer; genistein; chemotherapy; radiotherapy